Evaluasi Program Adiwiyata Mandiri Dalam Membentuk Karakter Peduli Dan Berbudaya Lingkungan Di SMPN 1 Pandaan - Luluk Nur Alfiyah; Abdulkadir Rahardjanto (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: Eradication of environmental problems Indonesia has a solution in the form of adiwiyata policies that are implemented in schools. The research objective evaluates the implementation of Adiwiyata after receiving the award with Adiwiyata components including 1) environmentally sound school policies; 2) development of an environment-based curriculum; 3) participatory-based environmental activities; 4) management of environmentally friendly supporting facilities in the context of forming a caring and cultured character in Junior High School 1 Pandaan. The method used in this research is descriptive qualitative which aims to evaluate the implementation of the adiwiyata program based on the Adiwiyata program component. Data collection techniques by direct observation, interviews, and documentation. The data validity technique is obtained through source and technique triangulation. The results showed that an evaluation of the results of environmentally sound policies to form a caring attitude and environmental culture had been carried out at Junior High School 1 Pandaan. Evaluation of the results of the implementation of an environment-based curriculum in shaping culture and caring for the environment is only carried out 60% of teachers in integrated learning and has an impact on the application of students' environmental knowledge. Evaluation of the results of participatory-based environmental activities in shaping cultural character and caring for the environment has been carried out but has decreased in cooperation with outsiders and its role as resource persons An evaluation of the results of the management of environmentally friendly supporting facilities in the formation of a caring and cultured character of the environment has been carried out but needs to be further improved in the improvement and management of infrastructure.Keywords: Evaluation, Self Adiwiyata, Character Abstrak: Pengentasan soal masalah lingkungan Negara Indonesia memiliki solusi berupa kebijakan adiwiyata yang diberlakukan di sekolah. Tujuan penelitian mengevaluasi pelaksanaan Adiwiyata pasca diterimanya penghargaan tersebut dengan komponen Adiwiyata meliputi: 1) kebijakan sekolah berwawasan lingkungan; 2) pengembangan kurikulum berbasis lingkungan; 3) kegiatan lingkungan berbasis partisipatif; 4) pengelolaan sarana pendukung ramah lingkungan dalam rangka membentuk karakter peduli dan berbudaya lingkungan di SMPN 1 Pandaan. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif yang bertujuan mengevaluasi pelaksanaan program adiwiyata berdasarkan komponen program Adiwiyata. Teknik pengumpulan data dengan cara observasi langsung, wawancara dan dokumentasi. Teknik keabsahan data diperoleh melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa evaluasi hasil kebijakan berwawasan lingkungan untuk membentuk sikap peduli dan budaya lingkungan telah dilaksanakan di SMPN 1 Pandaan. Evaluasi hasil pelaksanaan kurikulum berbasis lingkungan dalam membentuk budaya dan peduli lingkungan hanya dilaksanakan 60% guru dalam pembelajaran terintegrasi dan berdampak pada penerapan pengetahuan lingkungan siswa. Evaluasi hasil kegiatan lingkungan berbasis partisipatif dalam membentuk karakter budaya dan peduli lingkungan telah dilaksanakan namun mengalami penurunan dalam kerja sama dengan pihak luar dan perannya menjadi nara sumber. Evaluasi hasil pengelolaan sarana pendukung ramah lingkungan dalam pembentukan karakter peduli dan berbudaya lingkungan telah dilaksanakan namun perlu ditingkatkan lagi dalam peningkatan dan pengelolaan sarana prasaran.Kata kunci: Evaluasi, Adiwiyata Mandiri, Karakter